Mechanical behavior, compressibility, and microstructural analysis of problematic soil through a green soil stabilization approach - Azam F.A.A.; Che Omar R.; Roslan R.; Baharudin I.N.Z.; Razman M.Z. (Elsevier B.V., 2025)
Researchers have explored various materials and methods to improve the strength and stabilization of peat soil for construction. Deep peat soil's significant compressibility, low bearing capacity, and high creep potential present major challenges in geotechnical engineering. In this paper, the unconfined compression strength (UCS) and oedometer testing were conducted to determine peat strength and compressibility behavior after being stabilized with a bio-cement called vege-grout, derived from fermented vegetable waste. Soil stabilized with 5 %, 10 %, 15 %, 20 %, and 25 % vege grout was cured for up to 8 weeks before undergoing UCS testing. The finding showed that, in between 4 and 6 weeks of the curing period, the UCS of the peat stabilized with vege-grout exhibiting substantial mechanical strength at all vege-grout inclusion levels. The results showed optimum strength improvements, with a 449 % increase in UCS at 15 % vege-grout after 8 weeks. At the optimal percentage, vege grout's cementitious properties bind peat particles, densify the matrix, and enhance soil strength and load-bearing capacity. The coefficient of consolidation (Cv) also improved, reducing settlement from 23.34 7.8 m2/year to 7.13 3.5 m2 per year over increasing effective stress. The significant improvement in strength and compressibility of peat after treatment with 15 % vege grout demonstrates the effectiveness of vege grout as a peat stabilizer and highlights its potential as an alternative to chemical stabilizers for foundation applications. ? 2024